Effect of High-Induction Magnetic Stimulation on Elasticity of the Patellar Tendon - Prucha, Jaroslav; Socha, Vladimir; Sochova, Viera; Hanakova, Lenka; Stojic, Slobodan (Journal of healthcare engineering, 2018)
Nowadays, a high-induction magnetic stimulation is starting to be increasingly applied as a biophysical stimulation in the conservative treatment of the degenerative locomotor system diseases. These are mainly in correlation with the changes in soft tissue elasticity, which should be positively influenced by the flow-induced electrical currents of high current density during high-induction magnetic stimulation. This assumption was verified within the interventional and prospective study using the ultrasound elastography. The group consisted of 6 volunteers, whose elasticity of the patellar tendons was measured using the 2D shear-wave ultrasound elastography. The volunteers were then exposed to a 20-minute high-induction magnetic stimulation session with a frequency of 20 Hz, in 2 s package intervals, with a 5 s pause, and a induced electric current density of 100 Am-2 in the tendons area. A tendon tension was measured five times for all volunteers, where mean tension at the marked area of the tendon, as well as the highest point tension indicated by the Q-Box, was monitored. The measurement results show that high-induction magnetic stimulation has an influence on the patellar tendon tension change, which occurred in the case of all involved volunteers when the patellar tension was decreased.
Keywords: Movement; Algorithms; Humans; ultrasonografie; lidé; Patellar Ligament; lidé středního věku; Middle Aged; Elasticity; Elasticity Imaging Techniques; Biophysics; Shear Strength; Ultrasonography; Male; ligamentum patellae; Adult; Healthy Volunteers; mužské pohlaví; zdraví dobrovolníci pro lékařské studie; Rehabilitation; elastografie; rehabilitace; dospělí; pružnost; biofyzika; algoritmy; pohyb; pevnost ve smyku